Epigenetics of oropharyngeal squamous cell carcinoma: opportunities for novel chemotherapeutic targets. Issue 1 (December 2017) - Lindsay, Cameron; Seikaly, Hadi; Biron, Vincent
Abstract Epigenetic modifications are heritable changes in gene expression that do not directly alter DNA sequence. These modifications include DNA methylation, histone post-translational modifications, small and non-coding RNAs. Alterations in epigenetic profiles cause deregulation of fundamental gene expression pathways associated with carcinogenesis. The role of epigenetics in oropharyngeal squamous cell carcinoma (OPSCC) has recently been recognized, with implications for novel biomarkers, molecular diagnostics and chemotherapeutics. In this review, important epigenetic pathways in human papillomavirus (HPV) positive and negative OPSCC are summarized, as well as the potential clinical utility of this knowledge. This material has never been published and is not currently under evaluation in any other peer-reviewed publication.